Factors related to the probability of suffering mental health problems in emergency care professionals - de la Cruz, Silvia Portero (Rev Lat Am Enfermagem, 2019)
OBJECTIVES: to evaluate the influence of burnout and coping strategies used by health professionals of the hospital emergency service on their mental health status and to determine sociodemographic and labor characteristics. METHOD: descriptive cross-sectional study in a sample of 235 nursing professionals and physicians who worked in four hospital emergency services. The Maslach Burnout Inventory, the General Health Questionnaire and the Inventario Breve de Afrontamiento-cope 28 were used as data collection instruments and specific and original questionnaires of sociodemographic and labor variables. Descriptive, quantitative and multivariate statistics were applied. RESULTS: the dimension of depersonalization, avoidance-centered coping and being a physician were related to the presence of somatic symptoms, anxiety, social dysfunction and depression. Increased professional experience was associated with greater social dysfunction among health personnel and increased number of patients was related to depressive symptoms among health professionals. CONCLUSIONS: the dimensions of emotional exhaustion and depersonalization, avoidance-centered coping, being a physician and a daily smoker increase the risk of a psychiatric case. The practice of daily physical exercise is a protective factor.